Confronting Extremism and Radicalisation in Afghanistan: Educative Approach - Saim, Khalid Kamal; El-Muhammady, Ahmad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Extremism and radicalisation are not a new phenomenon in Afghanistan. Since the end of Soviet occupation in 1989, Afghanistan underwent several phases of challenges, either in the form of political instability, economic crisis, civil war, or foreign intervention due to geopolitical interests. One of the most challenging problems that Afghanistan has been facing is the threat of extremism and radicalisation resulting from multivariate factors. Extremist ideologies such as Salafi-jihadism, the presence of radical ideologues, and foreign intervention inside Afghanistan has intensified the challenge of extremism and radicalisation. In light of this reality, this article seeks to analyse how the government of Afghanistan deals with the problem of extremism and radicalisation in their midst through an educative approach or educational programs that they implement in higher learning institutions. Specifically, this article seeks to examine to what extent the implementation of a nation-building module known as ‘The Islamic Moral System Module (I.M.S.M.) has been effective in mitigating the problem of extremism, radicalisation and, at the same time, nation-building in post-war Afghanistan. Using mixed methods, the article looks into the implementation of IMSM on undergraduate students at Balkh University in Afghanistan between 2017 and 2020. The implementation of the IMSM module indicates that the educative approach produced positive results in nation-building. However, the educative approach needs to be tailored according to the nature of the challenge and context of the historical background of the country.